Reinhard Marquaß Structural Analysis on Short Story "The Black Cat" by Edgar Allan Poe as the Learning Materials in CWPP - Wahyuningsih, Linda; Welasiyah, Slamet; Indriani, Lilia (Kajian Bahasa dan Sastra (KABASTRA), 2025)
In this article, the researchers focus on structural analysis in the short story “The Black Cat” using Reinhard Marquaß’s theory that emphasizes the importance of considering the structural elements of short stories, such as plot, character development, and theme, to appreciate their impact on readers. The purpose of this article analysis is to analyze the elements in this short story and help students learn about this short story, especially in Creative Writing Poetry and Prose (CWPP). This analysis uses qualitative research that produces descriptive data using an objective approach. This analysis found a plot with five descriptions, four characters and characterization, and three settings about time, place, atmosphere, and point of view in “The Black Cat” short story.